Reported Benefits of Yoga in Middle Schools: A Review of the Literature - Paul Caldarella; Malka S. Moya (Middle Grades Review, 2022)
Middle school is a time of adjustments in youth: physical, intellectual, and social changes often result in stress. Middle school students are vulnerable to academic, behavioral, and mental health problems. Yoga is an Indian discipline practiced for health and relaxation. School-based yoga programs are becoming increasingly common given their potential benefits for students. We conducted a literature review of studies of middle school-based yoga programs, focusing on the reported benefits for students. We identified and retrieved 12 studies from electronic databases including Education Resources Information Center, PsycINFO, and Google Scholar that met inclusion criteria; (a) examined the benefits of yoga as the primary intervention conducted in a middle school setting with students ages 10 to 15 years old, (b) was published by June 2022, (c) was reviewed either by a journal editorial board or by a student’s dissertation or thesis committee, (d) was available in English, and (e) a full text copy was available. Results of studies were synthesized by clustering findings into common domains. Study results suggested that middle school-based yoga interventions showed mental health, executive functioning, physical, social, and academic benefits for students. Yoga also showed benefits for middle school students who were stressed, anxious, or depressed, and those at risk. We provide considerations for those contemplating the implementation of yoga in middle schools.
Keywords: middle schools; yoga; adolescents; mental health; literature review